In Vitro Evaluation of Toxicant Influences on the Immune System. Issue 1 (15th June 2020) - Kasten‐Jolly, Jane; Lawrence, David A.
Abstract: Culture of human peripheral blood mononuclear cells (PBMCs) still remains a convenient and sensitive method for measurement of a person's immune system health. Basic elements of the process, namely PBMC purification and culture medium formulation, were first reported in the late 1960s, and the utility of the method for clinical application was reported in the 1970s. Clinically, the approach can provide information about the ability of an individual's immune system to fight off attacks by various pathogens. Over the years, the method has undergone many improvements, which have been aided by advancements made in flow cytometry technology and the development of fluorescent reagents. The protocols presented here describe flow cytometry–based techniques for PBMC culture that can be employed to determine the impact of various environmental toxicants on the immune system. A major advantage of these procedures is that they will provide information about a toxicant or drug through in vitro methods. As the relationship between exposures to certain toxicants and an individual's response to vaccinations has been of concern, one of the protocols described shows how to test an environmental toxicant for potential modification of the immune response to vaccine antigen(s). © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Measurement of cell proliferation Support Protocol 1 : Blood cell counting Support Protocol 2 : Measurement of cell viability after culturing Basic Protocol 2 : Identification of affected naïve/memory cell subsets